Xanthan gum production by Xanthomonas axonopodis pv. mangiferaeindicae from glycerin of biodiesel in different media and addition of glucose - Gondim, Tayssa Santos; Pereira, Roberto Guimarães; Fiaux, Sorele Batista (Acta Scientiarum. Biological Sciences, 2019)
Biodiesel production has been increasing yearly in Brazil. A large amount of glycerin is generated in this process and needs a correct destination. One possible use of this glycerin in crude form is in biotechnological processes. Xanthan gum is a commercial gum used primarily in the pharmaceutical and food industries as thickener, emulsifier and stabilizer. It is synthetized by species of the bacterium Xanthomonas generally from glucose. However, current research shows that species of this bacterium have the capacity to grow and synthesize the gum using glycerin from biodiesel. The aim of this study was to produce xanthan gum using glycerin from biodiesel production in medium with different nitrogen content, named complex and simple media. The kinetics of fermentation in simple medium showed a two-fold increase in gum production (3.16 kg.m-3) compared to the one in complex medium (1.46 kg.m-3) after 120 hours. The gum generated in this study showed chemical and rheological characteristics of xanthan gum. Glucose supplementation did not show an increase in xanthan production but did increase the consistency index and the behavioral index of solutions of this gum.